2013
DOI: 10.5455/2320-6012.ijrms20130809
|View full text |Cite
|
Sign up to set email alerts
|

Congenital malformations in multiple births

Abstract: Objective: The present study was done to know and compare the incidence of congenital malformations in singleton and multiple births in our hospital & compare with other studies. Methods: A retrospective study done by collecting the data from parturition register from Jan 2008 to Dec 2011 (4yrs) from Cheluvamba Hospital attached to Mysore Medical College and Research Institute. Total number of the live births, still births, and abortions> 20 wks were collected. Details of multiple births such as maternal age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
4

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
1
4
4
Order By: Relevance
“…This is against Best and Rankin, 2015 [48] who found increased rate of congenital heart disease among twins than singletons. This is against Menasinkai et al, 2013 [49] who found higher incidence of CA among same sex twins than singletons.…”
Section: Resultsmentioning
confidence: 72%
“…This is against Best and Rankin, 2015 [48] who found increased rate of congenital heart disease among twins than singletons. This is against Menasinkai et al, 2013 [49] who found higher incidence of CA among same sex twins than singletons.…”
Section: Resultsmentioning
confidence: 72%
“…There were similarities in twin characteristics in our population respect to previous studies, as high frequencies of very preterm (12.7% vs 13.6%), preterm (65.9% vs 41.7-59.9%) and very low BW neonates (13.9% vs 9.5%) [5,24], but there were differences in reported rate of congenital malformations in twinning (11%). This higher prevalence than previously reported (2-9%) [20,[25][26][27], is probably related to the presence in our institution of an obstetrical and surgical reference center for western Sicily. However, the study can be considered representative [20,[25][26][27], because stochastics of factor of chorionicity and type of malformations are normally distributed [28].…”
Section: Twin Characteristicscontrasting
confidence: 62%
“…This higher prevalence than previously reported (2-9%) [20,[25][26][27], is probably related to the presence in our institution of an obstetrical and surgical reference center for western Sicily. However, the study can be considered representative [20,[25][26][27], because stochastics of factor of chorionicity and type of malformations are normally distributed [28]. Previous studies have suggested that a discordant malformation in MC twins represents one of the more important clinical problems affecting a significant proportion of perinatal morbidity and mortality [16], and that the magnitude of the association between twinning and malformations varies by zygosity, with stronger association reported for MZ twins than for DZ twins except for a few particular birth defects (anotia/microtia, transposition of great arteries, CDH and craniosynostosis) [29].…”
Section: Twin Characteristicscontrasting
confidence: 62%
“…There were similarities in twin characteristics in our population respect to previous studies, as frequencies of very preterm (12.7% vs 13.6%), preterm (65.9% vs 41.7-59.9%) and very low BW neonates (13.9% vs 9.5%) [5,24], but there were differences in reported rate of congenital malformations in twinning (11%). This higher prevalence than previously reported (2-9%) [20,[25][26][27],…”
Section: Twin Characteristicscontrasting
confidence: 54%
“…is probably related to the presence in our institution of an obstetrical and surgical reference center for western Sicily. However, the study can be considered representative [20,[25][26][27], because stochastics of factor of chorionicity and type of malformations are normally distributed [28].…”
Section: Twin Characteristicsmentioning
confidence: 99%